2011
DOI: 10.1051/epjap/2011100294
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical approach for studying the MinD protein dynamics and energy landscape: a novel use of the spot tracking technique

Abstract: The dynamics of MinD proteins have been acknowledged as playing a central role in accurate cell division. In our study, a spot tracking technique (STT) was applied to track motion and quantitatively characterize the dynamic behavior of MinD proteins on the level of particle cluster in Escherichia coli. We focused on the time and spatial distribution of MinD proteins. With the STT technique, the main quantitative results are twofold: (i) dynamic local and global pattern formations and (ii) energy landscape. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Interestingly, it was suggested that transient interactions of MinE with the membrane following the release of MinD are essential for formation of this pole-topole oscillations (Hsieh et al 2010;Park et al 2011). Due to this dynamical behavior, the time-averaged MinD concentration on the membrane (and hence also that of MinC) is the highest next to the poles and the lowest around midcell (Kanthang et al 2011). Due to this concentration profile of MinC, the FtsZ ring will be prevented to form near the poles (i.e.…”
Section: Controlling the Position Of The Division Sitementioning
confidence: 99%
“…Interestingly, it was suggested that transient interactions of MinE with the membrane following the release of MinD are essential for formation of this pole-topole oscillations (Hsieh et al 2010;Park et al 2011). Due to this dynamical behavior, the time-averaged MinD concentration on the membrane (and hence also that of MinC) is the highest next to the poles and the lowest around midcell (Kanthang et al 2011). Due to this concentration profile of MinC, the FtsZ ring will be prevented to form near the poles (i.e.…”
Section: Controlling the Position Of The Division Sitementioning
confidence: 99%